(untitled) (Bodhi Path, 2023)
Religion is essential for human beings. Without religion, a human cannot live a meaningful life, thus the need for religion in human life. Every person is associated with some religion and follows the rules and regulations made by that particular religion. Therefore, every human being is connected with some religion. In the world, religions have been the driving force behind the development and growth of many countries in the past centuries. This era is also considered a revolutionary era from the social and cultural perspective. In India also, many great social reformers have emerged and among them, Lord Buddha’s influence on human history is unparalleled. In the history of religions, Buddhism holds a unique position. Buddhism is a non-theistic religion and it emphasizes on self-reliance and self-enlightenment. Many people’s well-being and happiness can be achieved through spreading kindness, compassion and by working for the welfare of the people. The development and expansion of the teachings of Buddha and his disciples was based on this concept of welfare for the people. Buddhism accepts the universality of suffering and considers the elimination of the cause of suffering as the ultimate goal. Buddhism does not believe in blind faith but instead, it emphasises on the acceptance of suffering as the fundamental characteristic of the worldly life. Buddha propounded the Four Noble Truths, which are the foundation of Buddhism, through his own experience and knowledge. The Four Noble Truths are, 1) the truth of suffering, 2) the truth of the cause of suffering, 3) the truth of the cessation of suffering and 4) the truth of the path leading to the cessation of suffering. Buddha emphasised on self-reliance and self-enlightenment.